The Declining Rice-Fish Farming: A Case Study from North Kerala - K.N. Nair, Vineetha Menon and R. Mahesh (Sociological Bulletin, 2004)
In the coastal regions of India, a complex and ecologically respon sive farming system has evolved over centuries. In this system, rice and fish cultivation alternates through a mechanism of water control. This paper discusses the evolution of the socio-political and institu tional arrangements in such an integrated farming system (known as kaipad cultivation) in Ezhome Panchayat in Kerala that emerged out of collective action, and documents how they could not be sustained. The decline of kaipad cultivation has been adversely affecting the livelihoods of a segment of agricultural labour households, especially the women and the elderly. There are several constraints to the revival of this cultivation. Nevertheless, reviving this is vital for eco restoration and to ensure justice to the disadvantaged people.